Fission yeast pap1-dependent transcription is negatively regulated by an essential nuclear protein, crm1. - Toda, T (1992)
The fission yeast pap1+ gene encodes an AP-1-like transcription factor that contains a leucine zipper motif. We identified a target gene of pap1, the p25 gene. The 5' upstream region of the p25 gene contains an AP-1 site, and by DNase I footprint analysis, we showed that the pap1 protein binds to the AP-1 site as well as to a 14-bp palindrome sequence. p25 is overproduced when the pap1+ gene is overexpressed, whereas p25 is not produced at all in the pap1 deletion mutant. p25 was previously found to be overproduced in strains carrying cold-sensitive crm1 mutations whose gene product is essential for viability and is thought to play an important role in maintenance of a proper chromosomal architecture. Deletion and site-directed mutagenesis of sequences upstream of the p25 gene demonstrated that the AP-1 site as well as the palindrome sequence are crucial for transcriptional activation either by pap1 overproduction or by the cold-sensitive crm1 mutation; pap1+ is apparently negatively regulated by crm1+. Moreover, we found that cold-sensitive crm1 mutations are suppressed by the deletion of pap1+, further indicating a close relationship between crm1+ and pap1+. The crm1 protein is highly conserved; the budding yeast homolog, CRM1, which complements the fission yeast cold-sensitive crm1 mutation, was isolated and found to also be essential for viability. These results suggest the functional importance of chromosome structure on the regulation of gene expression through the pap1 transcription factor.